Impact of Csr Activities on Consumers Perception: a Empirical Study: Understanding Consumers' Expectations and Perceptions of Corporate Social Responsibility (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The social responsibility of business is considered acomprehensive set of practices, programs and policies that are integrated intobusiness operations, supply and decision making in all channels of theorganization, where the organization operates, and includes responsibility forthe current and past actions and future impacts. Over the past 20 years, there hasbeen a radical change in the nature of triangular relationship betweenbusiness, government and society. No more that they can continue to act asindependent entities, regardless of the interest of the general public. Theevolution of the relationship between business and society has been a slowtransformation of a hardcore corporate philanthropy. In light of this context,the ' objective of this article is to analyze the expectations and perceptionsof consumers towards social responsibility. This paper seeks to know thedifference between expectations and perceptions of consumers about companiesabout their social responsibility, and this document also helps companiesunderstand consumer expectations about corporate social responsibility, so thatcompanies are able to perform out their duties in an appropriate manner.